(untitled) (Informatica, 2022)
LabView is used to design the system to monitor and control lab experiments remotely over the Internet. Web based embedded system is designed and presented in this paper along with required hardware to perform experiments remotely in allocated time slot. A unique system is designed to monitor and control room temperature remotely. To assess the performance of the designed system and the hardware, an experiment is designed to control room temperature remotely. The Temperature Control System (TCS) publish over the internet by using web server along with embedded live video of the equipment to control and change various required variables. LabView and the equipment from National Instruments is used to perform the experiment and the designed system can be controlled anywhere from the planet by using secure login detail only which exist in the database of server. As the experiments take long time to be completed and during this time the performer need to be presented in the Lab. By implementing this type of system, it will save the time of the performer and it can be utilized in other activities. Also by designing and implementing this approach students from other Universities can also utilized the hardware and collaboration between institutions will be enhanced. The designed system presented in this article shows promising results which are presented in coming sections of this paper. The performed experiments are recorded and banked in the repository of the institution for future reference along with results.